Till We Meet Again - Krantz, Judith (New York Bantam Books, 1989)
Eve dared. . . Eve, with passion that overruled her total innocence, ran away from home to live in unrepentant sin; won stardom singing on the stage of the Parisian music halls before Worlds War I; married into the world of international diplomacy; and become the greatest lady Champagne. Eve's younger daughter, Freddy, inherited all of her mother's recklessness. Growing up in California, she became a pilot by sixteen; throughout World War II she ferried war planes in Britain--a glorious redhead who captured men with one humorous, challenging glance. Eve's elder daughter, Delphine, exquisite, gifted, and wild, romped through the nightlife of Hollywood of the thirties. On a whim, she made a screen test in Paris and soon found herself a great star of French films. She chose to risk her life in occupied France because of a love that transformed her frivolity into courage.
Keywords: Women -- Mothers and Daughters